NASIONALISME DALAM CERPEN “MARDIJKER” KARYA DAMHURI MUHAMMAD: KAJIAN POSKOLONIALISME - Emma Rahmawati Fatimah (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Abstract This writing tries to see nationalism reflected from a short story entitled “Mardijker” by Damhuri Muhammad using postcolonial perspective. This short story also contain historical background about Belanda Depok, a group of slaves who work for Dutch landlord in Depok, Cornelis Chastelein, which later he released all the slaves. Postcolonial perspective is used to identify nationalism reflected from the character of the story, whether it is a centrifugal or a centripetal nationalism. The analysis is done in contextual level of nationalism, which is considered as a will to establish a world which in that world, East can actualize their self in a free way, without any pressure from West. The nationalism that present in the short story is a centripetal nationalism which pulled back the memories to the past and considered that the world had been exist before and can be found again.Keywords: nationalism, postcolonialism, centripetal nationalism.